Russia and the politics of extraverted urbanism in the 2014 Winter Olympics and the 2018 FIFA World Cup - Golubchikov, Oleg; Wolfe, Sven Daniel (My University, 2020)
This chapter discusses the state’s role and the politics of space in a comparative analysis of the 2018 World Cup and 2014 Winter Olympics in the Russian Federation. Critiquing the hegemonic use of ‘the Putin factor’ as an all-explanatory epistemological narrative in understanding developments in the new Russia, the authors argue that the two sports mega events have been critical for Russia’s internal spatial restructuring, even though they may still be entangled, like the case of any games of this sort, with soft power and soft nationalism. While Sochi was more place-centric, the FIFA World Cup is allocated to 11 different cities primarily across the European part of Russia. What is emerging in many of the host cities is mixed and spatially variegated: some significant and welcome material investments (such as new airports and improved central roads) but also contested developments, neglected areas, and poor planning (like oversized infrastructure aimed at satisfying the short-term needs of the event rather than the longer term needs of residents). Overall, both events represent shifts in Russia’s regional policies and a return of the federal state to urban development after years of neglect of this domain, but also highlight the contradictions of the new politics of space. Hence, this chapter examines such developments and the geo-political dimension of sport in Russia.